Identifying gut microbiota Faecalibacterium as a potential biomarker for distinguishing visceral or subcutaneous obese population - Li, Yi; Wang, Senlin; Zhang, Song; Li, Ergan; Liang, Meifang; Li, Youqin; Liuli, Anke; Deng, Li; Liu, Yanjun; Zhang, Tongtong; Xin, Di; Li, Yongmei; et al. (Frontiers in Microbiology, 2025)
BackgroundObesity is a global health issue, with sharply increasing rates due to excessive food intake and reduced physical activity, leading to an increased risk of various chronic diseases, such as type 2 diabetes and cardiovascular diseases. Fat distribution plays a significant role in health, with visceral fat being particularly associated with metabolic syndrome. Currently, computed tomography (CT) and magnetic resonance imaging (MRI) are the gold standards for measuring visceral fat, but they are costly and involve radiation risks. The gut microbiota is closely related to obesity, and dysbiosis may lead to obesity and metabolic disorders. Research on the relationship between visceral fat and the gut microbiota can aid in the development of new diagnostic and therapeutic approaches.MethodsWe selected 31 participants with class II obesity (body mass index between 35 and 40) and divided those samples into two groups on the basis of their VSR (visceral-to-subcutaneous fat volume ratio) measured by CT, analyzed their fecal. Microbiota through 16S rDNA sequencing.ResultsResults reveal significant differences in microbial composition between the visceral and subcutaneous obesity groups through 16S analysis of their fecal microbiota. The visceral obesity group presented a greater abundance of the Blautia genus, whereas the subcutaneous obesity group presented a greater abundance of the Faecalibacterium genus. Species difference analysis and clinical correlation analysis revealed that Blautia and Faecalibacterium were associated with visceral and subcutaneous obesity, respectively, and played opposite roles. Moreover, in our validation cohort (n = 16), we also found that the subcutaneous obesity group had a greater abundance of the Faecalibacterium genus.ConclusionThis study measured visceral and subcutaneous fat volumes via CT and revealed that the composition of the gut microbiota is related to the type of obesity. In addition, we found that Blautia and Faecalibacterium were associated with visceral and subcutaneous obesity, which provides new insights for the diagnosis and treatment of obesity.